Effects of l‐lysine/l‐arginine on the emulsion stability, textural, rheological and microstructural characteristics of chicken sausages. (9th September 2017) - Zhu, Xiaoxu; Ning, Cheng; Li, Shiyi; Xu, Peng; Zheng, Yadong; Zhou, Cunliu
Summary: The effects ofl ‐lysine (Lys), l ‐arginine (Arg) and soya protein isolated (SPI) on the physicochemical properties of chicken sausages were investigated. The results showed that the addition of Lys/Arg significantly decreased total expressible fluid and expressible fat, but significantly increased hardness, springiness, cohesiveness and chewiness of chicken sausage. Moreover, Lys and Arg were more effective than SPI. Rheology indicated that Lys/Arg increased final storage modulus and final loss modulus. Also, scanning electron microscope and confocal laser scanning microscopy disclosed that Lys or Arg was conducive to the formation of regular and uniform oil droplet surrounded integrate membrane. Overall, Lys/Arg exhibited a potential in the preparation of emulsion‐type meat products. Abstract : The tentative mechanism of Lys/Arg improve the ES of meat products.